Platelet Lysate Enhances Efficiency of Cryopreservation of Mesenchymal Stromal Cells - Rogulska, Elena Yu.; Petrenko, Yuriy A. (Problems of Cryobiology and Cryomedicine, 2014)
N/A Â Probl Cryobiol Cryomed 2014; 24(2):161.